Investigating the effect of conventional chemotherapies, Cisplatin and Doxorubicin, in combination with a nuclear transport inhibitor, INI-43, on cerfical cancer cells - Wilensky, Gabriella (Division of Medical Biochemistry, 2024)
Background: Cervical cancer is the most common gynaecological cancer in South Africa, and the burden of disease remains high across the developing world. Like with many other cancers, treatment is limited due to drug resistance and adverse side effects. To overcome these limitations, it has become of interest to inhibit multiple pathways that cancer cells are reliant on, using combination therapies to induce maximal killing of cancer cells. Conventional chemotherapies used in the treatment of cancer include Cisplatin and Doxorubicin, both firstline drugs often used in combination with other treatments. Our laboratory has a focus on identifying novel therapeutic targets and found that Kpnβ1, a member of the nuclear transport protein family is overexpressed and necessary for the survival of cervical cancer cells. Inhibition of Kpnβ1 with a novel Inhibitor of Nuclear Import; INI-43 inhibits Kpnβ1- associated nuclear import pathways and results in cancer cell death. This study investigated the potential of Cisplatin and Doxorubicin when used in combination with INI-43 as an anticancer approach. Methods: Cervical carcinoma cell lines, HeLa, ME-180 and SiHa, were treated with INI-43, Cisplatin and Doxorubicin individually or in combination with each other at fixed ratios. Cell viability was measured by the MTT assay and the Chou-Talalay method was adopted to investigate the nature of the drug interactions in the combination treatments. The Caspase3/7 Glo Assay and Western blot analysis were performed to identify markers of apoptotic death, Caspase-3/7 activation and PARP1 cleavage, respectively, in single and combination treated cells. gH2AX was also investigated via western blot analysis to determine levels of DNA damage in single and combination treated cells. Results: Combination index values were determined to be below 1 at all levels of cell death after treatment with INI-43 and Cisplatin and INI-43 and Doxorubicin combinations, in HeLa, ME-180 and SiHa cell lines, indicating a synergistic effect. Additionally, enhanced levels of PARP1 cleavage were detected in combination treated cells relative to those treated with individual drug doses, indicating that the observed synergism is attributed to both decreased cell viability and elevated levels of apoptotic cell death. Non-cancer ARPE-19 cells were unaffected by single agent treatments and, more importantly, remained unaffected after treatment with drug combinations which resulted in enhanced cell death in the cervical cancer cell lines tested. Conclusion: INI-43, when combined with Cisplatin or Doxorubicin, results in synergistic cytotoxic effects in cervical cancer cells of different histological origins. These results suggest that combining conventional chemotherapies with targeted inhibitors of nuclear import pathways, has potential as an anti-cancer approach that warrants further investigation.